2020
DOI: 10.1093/mnras/staa859
|View full text |Cite
|
Sign up to set email alerts
|

To TDE or not to TDE: the luminous transient ASASSN-18jd with TDE-like and AGN-like qualities

Abstract: We present the discovery of ASASSN-18jd (AT 2018bcb), a luminous optical/UV/Xray transient located in the nucleus of the galaxy 2MASX J22434289-1659083 at z = 0.1192. Swift UVOT photometry shows the UV SED of the transient to be well modeled by a slowly shrinking blackbody with temperature T ∼ 2.5 × 10 4 K, a maximum observed luminosity of L max = 4.5 +0.6 −0.3 ×10 44 erg s −1 , and a total radiated energy of E = 9.6 +1.1 −0.6 × 10 51 erg. X-ray data from Swift XRT and XMM-Newton show a transient, variable X-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 129 publications
2
40
0
Order By: Relevance
“…TDEs are typically characterized by smoothly declining optical light curves, and the handful of discrepant examples such as PS18kh (Holoien et al 2019) and 2018fyk/ASASSN-18ul (Wevers et al 2019) tend to display atypical features like rebrightenings and plateaus only in their ultraviolet (UV) light curves, thought to be connected with processes in the accretion disk. The fluctuations in optical light curves shown by 2020nov and 2021ehb in our sample are perhaps similar to those seen in ASASSN-18jd, whose nature as either a TDE or a new class of nuclear transient is still unclear (Neustadt et al 2020). The rebrightening episode of 2020acka, though classified as a TDE by Hammerstein et al (2021b), resembles that of ZTF19abvgxrq/2019pev (also included in our sample; see below), which has been proposed as a member of the Trakhtenbrot AGN (Trakhtenbrot et al 2019) by Frederick et al (2021).…”
Section: Bumpy Extragalactic Transient Categoriessupporting
confidence: 73%
“…TDEs are typically characterized by smoothly declining optical light curves, and the handful of discrepant examples such as PS18kh (Holoien et al 2019) and 2018fyk/ASASSN-18ul (Wevers et al 2019) tend to display atypical features like rebrightenings and plateaus only in their ultraviolet (UV) light curves, thought to be connected with processes in the accretion disk. The fluctuations in optical light curves shown by 2020nov and 2021ehb in our sample are perhaps similar to those seen in ASASSN-18jd, whose nature as either a TDE or a new class of nuclear transient is still unclear (Neustadt et al 2020). The rebrightening episode of 2020acka, though classified as a TDE by Hammerstein et al (2021b), resembles that of ZTF19abvgxrq/2019pev (also included in our sample; see below), which has been proposed as a member of the Trakhtenbrot AGN (Trakhtenbrot et al 2019) by Frederick et al (2021).…”
Section: Bumpy Extragalactic Transient Categoriessupporting
confidence: 73%
“…Ne V λ3426, when observable, is typically associated with AGN, and is present in the spectra of these sources. Strong He II profiles, although somewhat rare in association with normal stochastic AGN variability (Neustadt et al 2020), have been observed before and interpreted as the signature of a sudden enhancement of accretion (e.g. Trakhtenbrot et al 2019a;Frederick et al 2019).…”
Section: Association Of the Transients With Agnmentioning
confidence: 78%
“…The host-subtracted UV/optical SEDs of TDEs (e.g., Holoien et al 2014Holoien et al , 2016a and some AGN flares (e.g., Neustadt et al 2020) are well-fit as blackbodies. While in AGN the geometry of the emitting region is likely nonspherical and the emission is at least partly non-thermal, a simple blackbody fit should provide a reasonable estimate of the size and luminosity of the optically thick, Note-Synthetic host photometry computed from the Monte Carlo sampling of host galaxy SED fits with FAST.…”
Section: Blackbody Fitsmentioning
confidence: 85%